Induction Of Leaf Spot Resistance And Improvement In Quality Of Amaranth Through Mutation - Binu Venuganan Panickar (Department of Olericulture, College of Horticulture, 2003)
The present study on 'Induction of leaf spot resistance and improvement in quality of amaranth through mutation' was carried out in the vegetable research field of the Department of Olericulture, College of Horticulture, KAU, Vellanikkara with the objective of standardizing the optimum dose of gamma ray for inducing variability and to study the differential response of the mutagen on growth parameters, leaf spot infection and biochemical attributes in MI and M2 generation. Based on the survival percentage the LDso was fixed as 400 Gy and doses below that were tried. In general, a progressive decline in germination percentage, survival percentage, plant height, branches per plant, leaf length, leaf width, leaf stem ratio and vegetable yield per plant was noticed with increase in dosages of gamma rays in MI generation. Increased content of Beta carotene, vitamin C and decreased content of oxalate and nitrate could be found at lower doses. Analysis of induced variability in M2 generation showed a negative shift in mean values for all the characters except days to flowering and crop duration. The mean performance was found to be minimum for higher doses and maximum for control and lower doses. Stimulatory effects could be noticed for plant height, leaf length, vegetable yield per plant, Beta carotene and vitamin C. This clearly demonstrated that a positive response to selection can be created by gamma rays in amaranth. Observations taken on disease severity at so" day after transplanting revealed that plants at 100 Gy dose showed less leaf spot disease infection whereas control and 400 Gy dose were highly susceptible to the disease. Quantitative analysis of the viable mutations revealed that the spectrum was much wider in A. hypochondriacus than A. tricolor. With further research on the same, it may be possible to isolate desirable mutants in the further generations.